P126 The 2014/15 european collaborative clinical group (ECCG) service evaluation on the management of pelvic inflammatory disease. (18th May 2015) - Etomi, Omome; Ahmed, Sabah; Brooks, Ben; Donders, Gilbert; Gomberg, Mikhail; Greenhouse, Peter; Jensen, Jorgen; Judlin, Phillipe; Ross, Jonathan; Clarke, Emily; Patel, Raj
Abstract : Background: Pelvic Inflammatory Disease (PID) describes a broad spectrum of disease primarily diagnosed clinically, with signs and symptoms lacking both specificity and sensitivity. Mycoplasma genitalium (MG) is being increasingly implicated in cases of non-chlamydial non-gonococcal PID. The core principle of the management of PID remains to maintain a low threshold for diagnosis and treatment to prevent long-term sequelae. Aim: To evaluate the current management of PID amongst sexual health physicians across Europe against the current European guidelines. Methods: A clinical scenario based questionnaire was developed by a panel of European experts on PID, and this was disseminated to a group of 120 sexual health physicians across 38 countries who are members of the European Collaborative Clinical Group (ECCG) – a network of sexual health specialists who conduct questionnaire based research across the European region. Results: Provisional results demonstrate variation in practice across Europe and this is most marked in routine testing for and treatment of MG-associated PID, factors influencing the choice of antibiotic therapy, and action taken when an intrauterine device or system is in situ . Full results will be available by the conference. Conclusion: The management of PID varies across Europe and is not always in line with current European guidelines. There is a need for ongoing Europe wide education to ensure that patients are receiving evidence based care. Furthermore, there are issues in clinical practice which are currently not covered by the European guidelines and these need to be reviewed to provide physicians with appropriate guidance.